Antidepressant Potential of Diphenyl Dimethyl Bicarboxylate (DDB) in a Modified Forced Swimming Test - Amal Mahfoz (Ain Shams University, 2021)
Biphenyl Dimethyl Dicarboxylate (DDB); is an analogue of schisandrin C, a component isolated from Fructus Schisandrae Chinensis. It is now attracting growing attention for its polypharmacotherapeutic properties as an antiviral, hepatoprotective, and immunomodulator. It's been additionally possessed neurobehavioral impacts on experimental animals. Thus, the wide use of DDB, along with its neurobehavioral impacts; has encouraged us to study its antidepressant potential using the forced swimming test (FST). Furthermore, the protocol for FST was modified by combining it with the tail suspension test. The effect of DDB (100 mg/kg/day, p.o., 7 days) on combined technique was evaluated against fluoxetine (15 mg/kg, i.p., single dose). In the end, the brains were dissected; serotonin (5-HT), dopamine (DA), and norepinephrine (NE) levels were measured. The results demonstrated that DDB decreased immobility in FST time as fluoxetine. Furthermore, DDB elevated 5HT, NE, and DA. DDB may be useful as a supportive antidepressant drug in hepatic diseased patients. However, more clinical studies are needed to ensure its safety.